SAT0251 Vascular Involvement in Scleroderma; Phenotypic Variability with Different Mechanistic Pathways. (15th July 2016) - Suliman, Y.A.S.; Kafaja, S.; Alemam, M.F.; Valera, I.; Jackson, N.; Alkady, E.; Mosad, E.; Mansour, E.; Fathi, N.; Marsh, E.; Morales, W.; Fitzgerald, J.; et al.
Abstract : Background: Vascular involvement is an early feature of Systemic sclerosis (SSc) and has a major role in the phenotypic presentation of the disease. Recent data showed overlapping pathways between bone and vascular biology. OPG was shown to enhance neovascularization and protects micro-vascular endothelial cells (ECs) from apoptosis; Signaling studies on human umbilical vein endothelial cells (HUVECs) showed that OPG is a positive regulator of micro-vessel formation acting as a pro-angiogenic molecule, OPG is also increased in idiopathic pulmonary artery hypertension (iPAH). RANKL, has shown anti-angiogenic properties with subsequent inhibition of EC proliferation. Vinculin: in turn was shown to be over expressed in ECs and may have a role in the impaired angiogenic process seen in SSc. we hypothesize that overexpression of Vinculin in SSc may trigger anti-vinculin antibodies (abs) which may contribute to vasculopathic features in SSc. Objectives: We wanted to investigate the role of OPG/RANKL, anti-Vinculin antibodies as biomarkers of vascular dysfunction such as PAH and ulcers in SSc. Methods: Serum levels of OPG/RANKL and Anti-Vinculin abs were measured by ELISA in serum obtained from 70 SSc patients. Correlations between serum levels and clinical aspects of SSc patients (skin ulcers, PAH) were done by linear regression analysis. Clinical assessments, procedures, questionnaires and lab results were obtained from medical charts for clinical correlations. Results: 70 SSc pts, mean age 56 yrs, 58females, 23 (32%) pts with PAH, active ulcer in 19 (28%) (table 1). Higher OPG was associated with older age (p=0.003), lower Ulcer visual analogue scale (VAS) (p=0.036), lower FEV1 (p=0.042). No association was found with PAH (p=0.50). Higher RANKL levels were associated with presence of skin ulcers (p=0.039). There was no evidence of differential prediction of OPG and RANKL for any of the clinical variables, given PAH status, using linear regression. In contrast, Linear regression analysis for anti-vinculin identified PAH (p value<0.052) as significant predictors of higher anti-vinculin in SSc patients. Further regression analysis for predictors of PAH with higher vinculin levels revealed smoking (current or former) as a significant (p value <0.01) predictor. Conclusions: Higher RANKL correlated with the presence of skin ulcers while Higher OPG correlated Lower ulcer VAS regardless of the PAH status. Anti-vinculin antibodies correlated with PAH regardless the skin ulcer status of our SSc patients. Although vascular dysfunction has a major role in driving the various morbidities in SSc (ulcer and PAH), Our Study Suggests that Different pathogenic pathways are involved in skin ulcer and Pulmonary artery hypertension. Disclosure of Interest: None declared